An Economic Evaluation Of Problems Faced By Self Help Groups In Nanguneri Taluk Under The Kalaignar Magalir Urimai Thittam Era. - Dr. P. Anici Subha; Dr. P. Anici Subha; Dr. E. Walsa Ebenezer; Dr. E. Walsa Ebenezer (Revista Electronica de Veterinaria, 2024)
Women’s Self-Help Groups (SHGs) are small, voluntary associations of women, generally from similar socio-economic backgrounds, who come together to promote savings, provide access to credit, and engage in income-generating activities. These groups are designed to foster financial inclusion, encourage entrepreneurship, and empower women socially and economically. The concept of SHGs in India gained prominence in the 1980s and 1990s as a strategy for poverty alleviation and rural development. NABARD’s SHG-Bank Linkage Programme (1992–93) institutionalized access to formal credit for rural women, making SHGs a crucial tool for women’s empowerment. Over time, SHGs have not only facilitated financial transactions but also provided platforms for skill development, literacy, health awareness, and participation in community decision-making.